From Russia with Love: The Impact of Relocated Firms on Incumbent Survival - Stephan Heblich; Oliver Falck; Christina Günther; William R. Kerr (Verein für Socialpolitik, 2010)
Identifying the impact of local firm concentration on individual firm performance is likely to produce a selection bias related to the positive effects of local concentration if agglomeration economies and natural advantages coincide. We overcome this problem by exploiting exogenous variation arising from a natural experiment. When Germany was divided after World War II, a great many firms fled the socialist East to prevent expropriation and located in random West German regions. Based on micro-level data for the population of firms in the machine tool industry from 1949-2002, we identify the impact of relocated firms on incumbent firms' survival. We find a negative effect on incumbent survival, suggesting that the costs of increased competition dominate the potential benefits of agglomeration.
Keywords: R10; L10; H25; 330; Agglomeration Economies; Competition Effect; Natural Experiment